1984
DOI: 10.1007/bf00254822
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of waxy gene expression in rice endosperm

Abstract: In order to examine the effects of different alleles on the gene expression at the waxy locus, the Wx gene product which controls the synthesis of amylose was isolated from endosperm starch of rice plants and analysed by electrophoretic techniques. The major protein bound to starch granules was absent in most of waxy strains and increased with the number of Wx alleles in triploid endosperms, suggesting that the major protein is the Wx gene product. In addition to wx alleles which result in the absence or drast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
285
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(299 citation statements)
references
References 19 publications
14
285
0
Order By: Relevance
“…This result is consistent with the endosperm-and pollen-specific expression of the waxy genes encoding GBSSI as reported in wheat (Ainsworth et al, 1993) and other cereals (Klosgen et al, 1986;Hirano and Sano, 1991;Baba et al, 1993). However, another granule-bound protein, GBSSII, which had characteristics similar to those reported for GBSSI (or waxy protein) in maize (Echt and Schwartz, 1981), rice (Sano, 1984), wheat (Yamamori et al, 1992), potato (Vos-Scheperkeuter et al, 1986), and pea (Smith, 1990), was detected in pericarp tissue. GBSSII was strongly bound to the starch granules, could not be detected in the soluble fraction, and its relative molecular mass was close to those reported for GBSSIs.…”
Section: Discussionsupporting
confidence: 69%
“…This result is consistent with the endosperm-and pollen-specific expression of the waxy genes encoding GBSSI as reported in wheat (Ainsworth et al, 1993) and other cereals (Klosgen et al, 1986;Hirano and Sano, 1991;Baba et al, 1993). However, another granule-bound protein, GBSSII, which had characteristics similar to those reported for GBSSI (or waxy protein) in maize (Echt and Schwartz, 1981), rice (Sano, 1984), wheat (Yamamori et al, 1992), potato (Vos-Scheperkeuter et al, 1986), and pea (Smith, 1990), was detected in pericarp tissue. GBSSII was strongly bound to the starch granules, could not be detected in the soluble fraction, and its relative molecular mass was close to those reported for GBSSIs.…”
Section: Discussionsupporting
confidence: 69%
“…Both patterns resembled each other but one band positioning at about 60,000 molecular weight (MW) was detected only in the lane of the white-core region. Sano (1984) reported that the Wx protein, an enzyme for amylose synthesis, had a MW size of 60 k Dalton (Da) and isoelectric point (pI) value of 7.0. Then, 2D-PAGE was performed in order to know whether the protein with a size of 60,000 MW detected by SDS-PAGE was the Wx protein or not.…”
Section: Resultsmentioning
confidence: 99%
“…The amylose in grain is synthesized by granule-bound starch synthase, a product of waxy (wx) locus (Nelson and Rines 1962). In nonglutinous rice, two wild type alleles of the wx locus, Wxa and Wx-b, have been recognized and the expression of the Wx-a gene was 10-fold higher than that of the Wx-b gene at the protein level (Sano 1984). The Wx-a gene is characteristic of indica rice and the Wx-b gene is found mainly in japonica rice (Sano 1984).…”
Section: Introductionmentioning
confidence: 99%
“…In nonglutinous rice, two wild type alleles of the wx locus, Wxa and Wx-b, have been recognized and the expression of the Wx-a gene was 10-fold higher than that of the Wx-b gene at the protein level (Sano 1984). The Wx-a gene is characteristic of indica rice and the Wx-b gene is found mainly in japonica rice (Sano 1984). Judging from the amylose content of the isogenic lines, Kikuchi (1988) suggested that Koshihikari, the most popular japonica rice variety in Japan, also harbours the Wx-b gene.…”
Section: Introductionmentioning
confidence: 99%